1999
DOI: 10.1016/s0014-5793(99)00706-1
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine protects epithelial cells against the oxidative imbalance due to Clostridium difficile toxins

Abstract: Toxins A and B from the anaerobic bacterium Clostridium difficile are the causative agents of the antibioticassociated pseudomembraneous colitis. At the subcellular level, they inhibit the Rho family GTPases, thus causing alterations of the actin cytoskeleton. The cytoskeletal integrity is also controlled by the redox state of cells. Therefore, we have evaluated whether an oxidative imbalance could be involved in the toxin-induced cytopathic effects. Our results indicate that both toxins induce oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
19
0
6
Order By: Relevance
“…At this dose, the scavenger could counteract the toxin-raised ROS production (Fig. 2a), as described previously (17). NAC was also able to diminish CNF1-induced up-regulation of TNF-␣, IL-6, and IL-8 gene expression (Fig.…”
supporting
confidence: 79%
“…At this dose, the scavenger could counteract the toxin-raised ROS production (Fig. 2a), as described previously (17). NAC was also able to diminish CNF1-induced up-regulation of TNF-␣, IL-6, and IL-8 gene expression (Fig.…”
supporting
confidence: 79%
“…Previous reports have noted oxidative stress pathways activated or up-regulated in response to C. difficile TcdA (26,27), and NAC is known to modify the oxidative imbalance in TcdBtreated cells (28). Although many of the previous studies of TcdA have suggested that the oxidative stress is due to mitochondrial ROS production, the dependence on Rac1 led us to speculate that the primary driver of oxidative stress in response to TcdB is NOX-mediated.…”
Section: Discussionmentioning
confidence: 88%
“…ROS (particularly intracellular H 2 O 2 ) generation is associated with TNF-␣-, Fas-, and angiotensin II-mediated apoptosis and various other stimuli (44 -46). In many cell types, including hepatocytes and fibroblasts, oxidative stress produces a severe F-actin reorganization (47)(48)(49)(50), whereas in human intestinal cell monolayers (Caco-2), H 2 O 2 enhances the chemical modification of actin and reorganizes F-actin (51,52). These findings suggest that a sustained increase in intracellular H 2 O 2 in GMF-␤-overexpressing cells may result in their vulnerability to apoptosis and F-actin reorganization.…”
Section: Discussionmentioning
confidence: 99%